PELATIHAN TARI BAGI SISWA SLB B-C HAMONG PUTRO SUKOHARJO, JAWA TENGAH - Rahmani, Dwi; Kuncoro, Jonet Sri; Murtono, Taufik (Institut Seni Indonesia Surakarta, 2024)
Dance training for students of SLB B-C Hamong Putro which is carried out in the PKM program aims to realize the welfare of persons with disabilities which cannot be separated from the role and support of the community. Society must work together with the government to provide equal rights for persons with disabilities. Specifically, this training is intended to support students' cognitive abilities which include 1) intellectual abilities, knowledge, understanding, and thinking skills, 2) affective abilities including aspects of feelings, emotions, interests, how to appreciate, and self-adjustment, and 3) psychomotor abilities including the physical abilities and skills needed in the basic movements of dance. The method used includes the group investigation stage, the drill stage, and the creative form stage. The PKM program produced an opera performance entitled Hug the Soul and a draft of a scientific article.